Clinical Characteristics of Patients with Retinal Vein Occlusion and Macular Edema at Cipto Mangunkusumo Hospital Kirana in Indonesia - Isfyanto, Isfyanto; Djatikusumo, Ari; Andayani, Gitalisa; Yudantha, Anggun Rama; Hutapea, Mario Marbungaran; Suryoadji, Kemal Akbar; Victor, Andi Arus (Indonesian Vitreoretinal Society, 2024)
Introduction: Retinal vein occlusion (RVO) is a significant retinal vascular disease, often resulting in macular edema and vision impairment. This study aims to investigate the clinical characteristics, management, and outcomes of RVO patients with macular edema at Cipto Mangunkusumo Hospital Kirana from January 2020 to December 2021. Methods: This retrospective descriptive study analyzed medical records of 85 RVO patients with macular edema. Demographic data, clinical characteristics, management approaches, and treatment outcomes were examined. Data were analyzed using SPSS. Results: Most patients were over 50 years old, predominantly male, and affected in one eye. Hypertension and diabetes mellitus were common comorbidities. Central RVO cases had worse initial visual acuity and macular thickness than branch RVO cases. Anti-VEGF injections were the primary therapy, and patients received an average of two injections in the first year. Macular thickness reduced after anti-VEGF injections, but visual acuity improvement was minimal. Conclusion: Patients with RVO and macular edema are often older males with systemic risk factors. Anti-VEGF injections are the primary treatment, with improvements in macular thickness but limited visual acuity gain. Patient education, comprehensive management, and public awareness are recommended to enhance RVO care. Further research to analyze parameter relationships is needed.